Power and responsibility building international order in an era of transnational threats - Jones ,Bruce (Brookings Institution Press, 2009)
"Makes the case for forming new international partnerships and revitalizing instruments of cooperation to address global challenges that post-WWII multilateral security systems cannot. Establishes a new conceptual foundation for international security: ?responsible sovereignty,? which entails obligations and duties and attitudinal changes toward other states as well one?s own"--Provided by publisher